FTC V. FACEBOOK OR BREAKING UP DOMINANT DIGITAL PLATFORMS IN THE TIME OF COVID-19: MOTIVES, RATIONALE, AND POSSIBLE ALTERNATIVES FROM A COMPETITION LAW PERSPECTIVE (EU and comparative law issues and challenges series (ECLIC), 2021)
The Federal Trade Commission of the United States (FTC) filed a Complaint against Facebook on 9th December 2020, in the midst of the COVID-19 crisis. While facing one of the biggest social and economic crises in American history, FTC has enough time and resources to (re)investigate Facebook’s acquisitions of Instagram and WhatsApp. This paper analyses motives and rationale behind the FTC’s Complaint requesting Facebook’s break-up and what could be possible alternatives from a competition law perspective. All the findings suggest that the FTC’s Complaint is politically motivated, and the competition authorities should enable digital platforms to expand. However, the expansion should be controlled, to ensure that the benefits for consumers are not undermined by relatively slower (not diversified) technological development.